Seed layer assisted growth of chemical bath deposited ZnO nanorods : influence of seed layer thickness / Rohanieza Abdul Rahman … [et al.] - Abdul Rahman, Rohanieza; Zulkefle, Muhammad AlHadi; Herman, Sukreen Hana; Alip, Rosalena Irma (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
Synthesis of zinc oxide (ZnO) nanorods by chemical bath deposition (CBD) was presented in this study. In this study, indium tin oxide (ITO) was used as the substrate, and the thickness of ZnO seed layer was varied, by varying the number of spin coating layers (1, 2, 3, 4 and 5 layers) while other growth parameters were remained constant. Based on the result obtained, the quality of ZnO nanorods was when te number of seed layer was increase. Based on the transmittance and absorbance value obtained, the optical energy band gap for all the growth ZnO nanorods were calculated. All of the ZnO nanorods thin films have the optical energy band gap in the range of 3.34-4.10 eV, which is approaching the theoretical band gap of ZnO (3.37 eV)